Comparative Analysis After Business Combination of Company Performance at PT Bank Mandiri Persero Tbk - Agustina R.T Sitompul; Debora Anjany Situmorang; Ibbie Falia; Elisabet Lumban Gaol; Riskana Natalia Br Bangun; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This research aims to determine the comparative performance of the company PT Bank Mandiri Persero TBK after carrying out a business combination. The method used is a comparative research method. This research uses the company’s financial performance which is determined using the liquidity ratio approach. Secondary data used in this research comes from the Bank Mandiri website and comes from PT Mandiri Tbk financial report data for 1999-2004. The research result show that there are variations in the results of the cash ratio and current ratio between 1994-1998 before implementing the business combination and 1999-2004 after the business combination, which shows an increase compared to before implementing the business combination